Pomona Lake Watershed Assessment: Preliminary Report - Nejadhashemi, A. P.; Gali, R.K.; Smith, C.M.; Mankin, K.R.; Wilson, R.M.; Brown, S.P.; Leatherman, J.C. (My University, 2009)
A preliminary assessment of the Pomona Lake Watershed in east central Kansas.
EP144_2009-02
Keywords: EP144; Environment and Natural Resources; EP